Strengthening laboratory management towards accreditation in Tanzania: The 13 years of remarkable revolutions in laboratory quality management system - Peter Richard Torokaa; Charles Massambu; Jacob Lusekelo; Regnald Julius; Alex Sifael Magesa; Mtebe Majigo; Agricola Joachim; Maria Ezekiely Kelly; Alice Kyalo; Nyambura Moremi (PLoS ONE, 2026)
Introduction The increase in demand of laboratory services and recent advancements in laboratory technologies underscore the importance of quality laboratory services in delivering accurate, reliable, and timely test results. As a strategy to ensure quality laboratory services in the country, Tanzania started to implement Strengthening Laboratory Management Towards Accreditation (SLMTA) program in 2010. We describe the revolutions made in laboratory quality management system across the 13 years of SLMTA implementation highlighting the impact and achievements attained following the modification of the generic SLMTA approach. Methodology We evaluated, described and summarized the 13 years of SLMTA implementation in Tanzania and the quality performance of medical laboratories enrolled into the program. The quality performance was evaluated based on the increase in number of SLMTA laboratories accredited under ISO 15189 by comparing the laboratories enrolled during the generic versus modified SLMTA program. Results Out of 138 SLMTA laboratories assessed by 2023 using the SLIPTA checklist, 81 (58.7%) scored 3 stars and above were enrolled in the accreditation process. Of the 81 enrolled laboratories, 50 (61.7%) achieved ISO 15189 accreditation status by 2023. There was a significant increase in number of accredited laboratories during the five years (2018–2023) of modified SLMTA compared to the eight years (2010–2018) of generic SLMTA (47/64 vs. 3/17, p = 0.021). In the context of level of healthcare delivery, most of the accredited laboratories (n = 47/50, 94%), belonged to the district level and above. Conclusion To the best of our knowledge, this is the first report of the modified SLMTA approach with remarkable results. The modified SLMTA program significantly improved the status and number of accredited laboratories in Tanzania. While the attained milestone demonstrates the SLMTA program’s effectiveness in strengthening quality of laboratory services, the significant achievements underscore the essence of monitoring, evaluation and learning of the implemented programs, and most importantly the need for strategies that contextualize and tailor the program for sustainability.